Analisis Perbandingan Pandangan Klasik dan Neoklasik terhadap Peran Pasar dalam Pembangunan Ekonomi - Dewi Jannati Asih Putri; Dhenia Lizariani; Nova Elisa; Pradita Mawardani; Hotman Hotman (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to compare classical and neoclassical economic perspectives on the role of the market in economic development and assess their relevance in the current Indonesian development context. The research uses a qualitative approach through library research by analyzing various economic literature sources. The findings reveal that classical economics emphasizes the importance of free markets without government intervention, while neoclassical economics incorporates individual rationality, marginal efficiency, and technological progress, while allowing for limited government intervention to address market failures. Both schools of thought agree that the market plays a central role in efficiently allocating resources. These findings provide important contributions for formulating adaptive and inclusive economic policies in developing countries such as Indonesia.